2012
DOI: 10.1186/1471-2296-13-47
|View full text |Cite
|
Sign up to set email alerts
|

Medical student attitudes towards family medicine in Spain: a statewide analysis

Abstract: BackgroundFamily and community medicine (FM) became a recognized specialty in Spain in 1978; however, most medical schools in Spain still lack mandatory core courses in FM. In order to explore the perceptions, expectations and level of information amongst medical students in Spain in relation to FM and PC, and the training in these areas in the curriculum of the Medical Schools, a survey was developed to be administered in medical schools every two years. This article presents data from the first questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
42
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 15 publications
5
42
1
7
Order By: Relevance
“…Based on our analyses we could con rm the ndings from the research about medical students' attitudes toward FM, that students value the social role of family medicine and family doctors more than their scienti c value (21). We could add that students also recognise the importance of organisational and management skills of family doctors and recognise them as teachers in organisational and management skills.…”
Section: Discussionmentioning
confidence: 67%
“…Based on our analyses we could con rm the ndings from the research about medical students' attitudes toward FM, that students value the social role of family medicine and family doctors more than their scienti c value (21). We could add that students also recognise the importance of organisational and management skills of family doctors and recognise them as teachers in organisational and management skills.…”
Section: Discussionmentioning
confidence: 67%
“…However, such change can be best accomplished by radical reform of graduate medical education, with emphasis on empathy and communication skills [18]. The reform can then bring about the development of different educational interventions for practical competencies, such as communication labs which help students to understand their future role as physicians and their relationship with patients, to develop self-confidence and prepare them for the first contact with patients [19,20]. The curricular reforms are directed to increasing practical work, problem solving, early contact with patients and greater bonding of students with their mentors [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Not only did many of the GPs we interviewed characterise HIV medicine as intrinsically interesting, they also viewed the ‘challenge and change’ involved in keeping up with scientific and clinical developments in this field as one of its major rewards. These accounts provide a counter perspective to the research literature which has consistently reported that medical students view general practice as offering insufficient ‘scientific-technical interest’ [63] or ‘intellectual content’ [71]. For example, a qualitative synthesis of the literature on choosing general practice reported a recurrent belief that general practice was less intellectually challenging than other areas of medicine, tending to treat only ‘common disease’ [67].…”
Section: Discussionmentioning
confidence: 99%